After Dictatorship: Politics of History and the Look Back to Look Forward (KULT_online, 2010)
The edited volume Nationen und ihre Selbstbilder (Nations and Their Seif-Images) focuses on the different formations of national societies and their historical self-conception since the reestablishment after war or system transformation in Europe. Beside mainly historiographic interpretative frameworks, also cultural and social sciences, linguistics and literature expand into the book. Particularly struggles about the interpretive predominance over historical events are being depicted which connect all contributions and thereby show similarities and differences in the reunited Europe.